Response characteristics of coal subjected to coupling static and waterjet impact loads. (March 2018) - Lin, Baiquan; Zou, Quanle; Liang, Yunpei; Xie, Jun; Yang, Huiming
Abstract: We have established an experimental system to investigate waterjet impact capacity and coal relaxation behaviors, with reference to hydraulic slotting. The results indicate that after waterjet impact, cracks with good connectivity can be observed on the surfaces of the coal specimen. Vibration acceleration can intuitively display waterjet impact capacity. The disturbance capacity of waterjet impact is significantly larger than that of drilling. The waterjet disturbance degree is defined by the vibration amplitude to quantitatively describe the waterjet impact capacity. The waterjet disturbance degree presents a decrease tendency after an initial increase with the increase in waterjet impact angle, presents a gradual increase tendency with the increase in the operating pressure, and presents an overall decrease tendency with the increase in the lateral coefficient. Based on the variations in axial and lateral pressures, we also proposed axial and lateral relaxation degree to quantitatively describe the coal behaviors under coupling static and waterjet impact loads. The axial relaxation degree gradually decreases and the lateral relaxation degree presents an opposite tendency with the increase in waterjet impact angle, and presents a gradual increase tendency with the increase in lateral coefficient. The research achievements can provide certain references for the application of hydraulic slotting in underground enhanced CBM recovery.